FACTORS FOR IMPROVING THE SOCIAL STATUS OF GIRLS WOMEN IN UZBEKISTAN IN THE PROGRESS OF GLOBALIZATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The scientific article is devoted to the analysis of important problems and factorsfor the elimination of gender problems in the Republic of Uzbekistan and their elimination. Inparticular, the necessity of organizing the activities of the training course “Postgraduate studies”,which is part of the fundamental research project on the topic “Modern educational infrastructure”,based on scientific and practical aspects, is shown.The scientific article uses a system-functional approach, a structural-functional approach, adialectical approach and important principles for the formation and development of civil society inUzbekistan and the ideas of national progress, positive national values. as a methodology
Keywords: globalization, women. gender problem, education, training, educational infrastructure, foundation of the third revival in Uzbekistan, graduate school for girls, activities of advanced training courses.